Physical Therapist’s Knowledge and Use of Medical Imaging in Clinical Practice: A Cross-Sectional Survey: Physical Therapist’s Knowledge - Quratulain, .; Afzal, Mamoona Tasleem; Aslam, Muhammad Aqeel; Wajid, Shanzay; Sairien, Sairish; Hasnat, Amina Mehak; Kashif, Muhammad; Ghaffar, Tamjeed (Pakistan Journal of Health Sciences, 2023)
Medical imaging plays an important and vital role in diagnosis and management of intervention during clinical practice. The ability to refer patients directly for diagnostic imaging could promote more efficient delivery of care. This study focuses on the confidence of the therapist to interpret diagnostic imaging and also how often do they refer for medical imaging. Objective: The aim of the current study was to measure the physical therapist’s knowledge and use of medical imaging in their clinical practice. Methods: This is a cross-sectional study and was conducted in Faisalabad in which 100 practicing physical therapists filled self-constructed questionnaire. SPSS 20 sheet for statistical analysis. Results: According to results 92.8% Therapists reported that they find significant for Medical Imaging in making clinical diagnosis, 90.1% Therapists reported that Medical Imaging is included in clinical diagnosis. Ninty six Therapists reported that no extra certifications for Medical Imaging is needed and 29.7% reported that they attended Continuous Professional Development (C.P.D) Programs Half of the Therapists said that their Source of knowledge on Medical Imaging is academic program and other half said that their knowledge is job exposure. Conclusions: This study concluded that Therapists find Medical Imaging significant in making clinical diagnoses. The majority of therapists indicated that they did not need additional Medical Imaging certifications. Half of the therapists said their main source of knowledge about Medical Imaging was academic programs, while the other half said job exposure.